High serum reproductive hormone levels at mid-pregnancy support Meishan pig prolificacy - Rong ZHOU; Ya-lan YANG; Ying LIU; Jie CHEN; Bing YANG; Zhong-lin TANG (Journal of Integrative Agriculture, 2023)
Increasing prolificacy is an important aim in the pig industry. Regions associated with litter size have been revealed, but detailed molecular mechanisms are unclear. The Meishan pig is one of the most prolific breeds, with higher prolificacy than the Yorkshire pig, which exhibits high feeding efficiency and lean meat yield. The ovary is the key organ determining reproductive traits during pregnancy by synthesizing and secreting reproductive hormones essential for conceptus maintenance. In this comparative multi-omics study of the ovary transcriptome, proteome, and metabolome on day 49 of pregnancy, we aimed to identify genomic, proteomic, and metabolomic differences between the ovaries of Meishan and Yorkshire pigs to reveal potential molecular mechanisms conferring high prolificacy. Meishan pigs demonstrated general downregulation of steroid biosynthesis and butanoate metabolism in the ovary during mid-pregnancy at both transcriptome and proteome levels but exhibited higher serum cholesterol, estradiol, and progesterone levels than Yorkshire pigs. We also identified several single-nucleotide polymorphisms in the genes of the steroid hormone pathway associated with litter number, average birth weight, and total litter weight. Lower biosynthesis rates but elevated serum levels of reproductive hormones during mid- and late pregnancy are essential for the greater prolificacy of Meishan pigs.